Genome-Wide Association Study Reveals Single Nucleotide Polymorphisms Associated with Tail Length and Tail Kinks in Piglets - Gerhards, Katharina; Egerer, Christiane; Becker, Sabrina; Willems, Hermann; Engel, Petra; Koenig, Sven; Reiner, Gerald; Justus Liebig University Giessen (My University, 2025)
Tail docking is still used in pigs to reduce the prevalence of tail biting, although it is purely symptomatic and contrary to animal welfare. Genetic selection for shorter tails might, however, help to avoid tail docking and has therefore been proposed. A genetic basis for tail length is known for many species. Variability in tail length, including moderate heritability, has also been demonstrated in pigs. The aim of the present study was to identify genetic markers for tail length and to define candidate genes. To this end, 140 piglets were phenotyped and genotyped at 3 days of age and a genome-wide association study was performed. Seven SNPs were mapped on chromosomes 1, 2, 6, 11, and 15. Two linked SNPs on chromosome 2 resulted in a functional amino acid exchange. The genotypes at the SNPs were only associated with small differences in relative tail length of up to 16.5% (short genotype versus long genotype at SSC15), but at the same time with the occurrence of malformations in the form of tail kinks. The small effect size and the association between tail length and tail kinks, together with the generally pure symptomatic effect on tail biting, argue against the applicability of selection for shorter tails in pigs.
Keywords: ddc:630